Analisis Keterampilan Membaca Pemahaman Literal Peserta Didik Kelas V SD Negeri 1 Rasau Jaya - Khalifah Mulyana; Yunika Afryaningsih; Nurhaidah Nurhaidah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the literal reading comprehension skills of grade V students of SD Negeri 1 Rasau Jaya. The research method used is qualitative method with descriptive qualitative approach. The population included in this study is grade V students at Sekolah SD Negeri 1 Rasau Jaya. The sample in this study was class V A students totaling 27 people, consisting of 15 male students and 12 female students. The technique used for classroom research is the test method. The data collection instruments used in this study were question sheets and literacy comprehension reading skills assessment sheets. Based on the results of data analysis that researchers have done, the results of literal comprehension reading skills in high grades of SD Negeri 1 Rasau Jaya using the test method, namely, 1) the main idea aspect obtained an average score of 74.07 and an average success percentage score of 74%, 2) the supporting idea aspect obtained an average score of 30.37 and an average success percentage score of 30%, 3) the aspect of understanding information (5W+1H) obtained an average score of 79.62% and an average success percentage score of 79%.